Applying Erikson’s theory of psychosocial development to understand autonomy development in children and youths with deafblindness: a systematic literature review - Rorije, Marianne; Damen, Saskia; Janssen, Marleen J.; Minnaert, Alexander (Frontiers in Education, 2023)
This systematic review revealed how children and youths with congenital deafblindness (CDB) exhibit autonomy characteristics and how caregivers perform autonomy support, which Erikson described as part of the first three stages of psychosocial development. This review comprises 22 studies that explicitly addressed one or more autonomy characteristics or autonomy support tasks. The results demonstrated that children and youths with CDB exhibited most characteristics of Erikson’s first stage (e.g., explorative behavior in their nearby environment and with objects within reach) and caregivers predominantly fulfilled autonomy tasks in the first stage (e.g., being present and near the child). In addition, children and youths with CDB exhibited independent acts at the second stage, although these were often limited to asking for or refusing concrete objects in the here-and-now situation. The limited degree to which the children with CDB exhibited autonomy characteristics from the second and third stages seems to co-occur with their struggle to develop symbolic communication. Additionally, the review revealed that caregivers supported autonomy by remaining present and nearby, even when autonomy support tasks from the second and third stages might be more appropriate in supporting the autonomy of children and youths with CDB (e.g., the second stage’s autonomy support task to balance between offering the child protection and encouragement, and the third stage’s task to support the child in taking initiative and setting goals). We recommend the use of a longitudinal video-feedback intervention that both supports the children’s and youths symbolic communication skills and supports caregivers in finding a balance between being present and nearby and fostering the autonomy characteristics of children and youths with CDB.